2018
DOI: 10.1242/jeb.179598
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous shutdown underlies acute cold tolerance in tropical and temperateDrosophilaspecies

Abstract: When cooled, insects first lose their ability to perform coordinated movements (CT) after which they enter chill coma (chill coma onset, CCO). Both these behaviours are popular measures of cold tolerance that correlate remarkably well with species distribution. To identify and understand the neuromuscular impairment that causes CT and CCO we used inter- and intraspecific model systems of species that have varying cold tolerance as a consequence of adaptation or cold acclimation. Our results demonstrate that CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 49 publications
5
59
1
Order By: Relevance
“…Insect thermal tolerance is an important factor mediating population range and dynamics, possibility of invasion, and response to global climate change (Addo‐Bediako et al, ; J. L. Andersen et al, ; Bellard et al, ; Youngsteadt et al, ). As such, great efforts have been devoted to understanding the molecular, physiological, and evolutionary underpinnings of insect thermal tolerance (Andersen et al, ; Andersen et al, ; Findsen et al, ; Macmillan et al, ; Macmillan et al, ). However, there are still gaps in our understanding of the behavioral consequences of cold stress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Insect thermal tolerance is an important factor mediating population range and dynamics, possibility of invasion, and response to global climate change (Addo‐Bediako et al, ; J. L. Andersen et al, ; Bellard et al, ; Youngsteadt et al, ). As such, great efforts have been devoted to understanding the molecular, physiological, and evolutionary underpinnings of insect thermal tolerance (Andersen et al, ; Andersen et al, ; Findsen et al, ; Macmillan et al, ; Macmillan et al, ). However, there are still gaps in our understanding of the behavioral consequences of cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…Cold exposure can lead to short-term disruptions in physiology, e.g., dysregulation of ion homeostasis , and long-term fitness consequences, e.g., reduced fecundity (Marshall & Sinclair, 2010;Rinehart et al, 2000). Disruption of membrane polarity and ion balance can cause a decline in neuromuscular cell survival and function (Andersen et al, 2017;Andersen et al, 2018;Findsen et al, 2016;Macmillan et al, 2014Macmillan et al, , 2015 assessing behavioral responses to cold stress using the RING assay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…70,71 Indeed, multiple studies have shown beneficial properties of SD, including preconditioning, upregulation of growth factors, and neurogenesisis. [72][73][74][75][76][77] In addition, previous studies in insects [78][79][80][81] and rodents 72,73,82,83 suggest that SD may play a neuroprotective role during ischemia. 1,84 It is possible that this protection is enabled by a "neuronal silencing" mechanism associated with SD 85 wherein metabolism is quickly shut down, possibly to conserve residual energy and minimize production of reactive oxygen species, potentially leading to an improved survival and outcome in reversible processes.…”
Section: Discussionmentioning
confidence: 99%